The THE ROLE OF AGE AND COMORBIDITIES ON THE OUTCOME OF CONFIRMED CLINICALLY CRITICAL COVID-19 PATIENTS TREATED WITH REMDESIVIR AT INDONESIA’S NATIONAL REFERRAL HOSPITAL - USMAN , Elly; KATAR , Yusticia (African Journal of Infectious Diseases (AJID), 2022)
Background: There is currently no viable pharmaceutical therapy for COVID-19 illness that has been validated. The use of remdesivir is one of the medications for which there is no consistent evidence of a significant therapeutic benefit or a meaningful effect on survival. Methods: A retrospective cohort study was used in this study. The subjects in this study were confirmed clinically critical COVID-19 patients who were treated at Dr. M Djamil Hospital Padang, one of Indonesia’s national referral hospitals, from January to June 31, 2021. The number of samples in this study was 90 patients. The Chi-square test was performed in bivariate analysis, and the odds ratio was calculated. SPSS version 17.0 was used to analyze the data. Results: The results of this study found that there was an association between ages 50-59 years (OR = 10.23, 95% CI 1.89-55.53), 60-69 years (OR = 4.58, 95% CI 1.25-16.76), and > 70 years (OR = 1.91, 95% CI 1.38 -9.59), comorbid diabetes mellitus (OR = 9.78, 95% CI 1.23-77.66), the number of comorbid > 1 (OR = 10.97, 95% CI 2.19-54.96, and the number of comorbid 1 (OR = 5.69, 95% CI 1.59- 20.41) with the outcome of confirmed clinically critical COVID-19 patients treated with remdesivir. Conclusion: The significance of age and comorbidities on the outcome of COVID-19 patients treated with remdesivir at Indonesia’s national referral hospital was confirmed in this study. This study could assist in the management of patient therapy, potentially decreasing morbidity and even patient mortality.